Cultural Goods Production, Cultural Capital Formation and the Provision of Cultural Services - Sao-Wen Cheng (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2005)
Cultural capital is assumed to benefit all members of society. It is accumulated through the consumption of cultural services and is diminished through depreciation. Using the stock of cultural goods, cultural services are provided by the cultural services industry; the stock of cultural goods is enlarged by the flow of new cultural goods created by individuals who are both consumers and creators of culture and whose utility is positively affected by the cultural goods they created. In the no-policy market economy, individuals tend to ignore the positive external effects of their cultural services consumption and creation of cultural goods on other individuals via augmenting cultural capital and cultural-goods stock. Consequently, less cultural capital and cultural-goods stock will be accumulated. The efficient allocation can be restored by introducing an appropriate subsidy that stimulates the consumers? demand for cultural services, and the creation of new cultural goods, promotes the accumulation of cultural capital and cultural goods.
Keywords: Z1; H3; H2; 330; cultural capital; cultural services; cultural goods; Kulturgut; Kulturökonomik; Theorie